Has water limited our imagination for aridland biogeochemistry? - Austin, Amy Theresa (2011)
The classic ecological paradigm for deserts, that all processes are controlled by water availability, has limited our imagination for exploring other controls on the cycling of carbon and nutrients in aridland ecosystems. This review of recent studies identifies alternative mechanisms that challenge the idea that all soil processes in aridlands are proximately water-limited, and highlights the significance of photodegradation of aboveground litter and the overriding importance of spatial heterogeneity as a modulator of biotic responses to water availability. Aridlands currently occupy >30% of the terrestrial land surface and are expanding. It is therefore critical to incorporate these previously unappreciated mechanisms in our understanding of aridland biogeochemistry to mitigate the effects of desertification and global change.